Collaborative Learning for Early Childhood Education - Ike Oktaviani, Herlina; Pramono Adi, Eka; Anisa, Nur; Astuti, Wuri; Gonadi, Leni; Wayan Sutama, I; Mulya Putra Pradana, Ilham (KnE Social Sciences, 2023)
If starting school at the age of seven was considered sufficient in the past, many parents now start their children at the age of toddlers. As a result, the teacher’s role is critical because it serves as a substitute for parents. Preschool teachers must be able to monitor children’s growth and development in addition to teaching because it affects their future. Parents and teachers must pay adequate attention and affection, educate, guide, and set a good example. Students collaborate in groups to achieve the common goal of each idea through collaborative learning. This aligns with the skills required in the 21st century, namely the 4Cs (creative thinking, critical thinking and problem-solving, communication, and collaboration). The research method employs descriptive qualitative research to describe early childhood teachers’ perceptions of collaborative learning’s current implementation. The participants in the study were 23 teachers who had implemented collaborative learning. Keywords: kwd